2022
DOI: 10.1002/star.202200053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications of Turmeric Starch by Oxidation, Phosphorylation, and Succinylation

Abstract: The goal of this study is to determine how different properties of turmeric starch are changed with oxidation, succinylation, and phosphorylation. These chemical reagents include sodium hypochlorite, octenyl succinic anhydride, sodium trimetaphosphate (STMP), and sodium tripolyphosphate, using the appropriate reagents (STPP). The isolated starch is modified using several chemical reagents, affecting the turmeric starch physicochemical, functional, thermal, and morphological properties. In hydration properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(43 reference statements)
0
8
1
Order By: Relevance
“…Its shows the stability‐indicating power of the method. All the results of degradation studies are shown in Figure 5(a–f) and Table 5 (Cholleti et al, 2022; Muchakayala et al, 2021; Muchakayala et al, 2022; Nakkala et al, 2022; Pydimarry, Cholleti, & Vangala, 2014; Pydimarry, Cholleti, & Venagala, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Its shows the stability‐indicating power of the method. All the results of degradation studies are shown in Figure 5(a–f) and Table 5 (Cholleti et al, 2022; Muchakayala et al, 2021; Muchakayala et al, 2022; Nakkala et al, 2022; Pydimarry, Cholleti, & Vangala, 2014; Pydimarry, Cholleti, & Venagala, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Native starch and oxidized starch reveal high (26.02 ± 0.04) and low (15.46 ± 0.12)% syneresis, respectively thus able to produce more stable starches. 67…”
Section: Modification Of Starch By Different Processesmentioning
confidence: 99%
“…Native starch and oxidized starch reveal high (26.02 ± 0.04) and low (15.46 ± 0.12)% syneresis, respectively thus able to produce more stable starches. 67 Regarding the solubility of starch, it is well known that heating leads to an increase in the solubility of Bambara groundnut starch. The oxidized starch has the highest solubility percentage as compared to other acetylated and modied starches.…”
Section: Chemical Processes For Modication Of Starchesmentioning
confidence: 99%
“…Total entropy formation decreases as Renault's magnetic field strength, number and number of dipoles increase. [20]. Furthermore, they concluded that its location per bipolar Studies related to the entropy formation of nanofluids and hybrid nanofluids in micro channels, mini channels and cavities have been reviewed for different boundary conditions, and there are significant changes in entropy formation variation when using two and three dipoles.…”
Section: Hybrid Nano Fluidmentioning
confidence: 99%